Does The XBRL Implementation and The Diversity of The Audit Committee Affect Quality of Financial Reports? - Nadya Rizki Amalia; R. Nelly Nur Apandi; Agus Widarsono (Nusantara Science and Technology Proceedings, 2020)
Problems in presenting non-uniform financial reports make it difficult for investors to process financial reports. So new technology is needed that can make investors and analysts easily process the information contained in financial reports. This research was conducted to obtain the relationship between the influence of XBRL on the quality of financial reports as moderated by the audit committee is IT knowledge. This research uses a quantitative approach with descriptive methods. Through descriptive research, the effect of using XBRL with the IT knowledge of the audit committee on the quality of financial reports is obtained. The research object in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2016. The results of this study indicate that XBRL does not affect the quality of financial statements. Also, the audit committee's IT knowledge does not affect the quality of financial reports. XBRL also does not influence the quality of financial statements, moderated by the IT knowledge audit committee. In 2016, many companies used XBRL, and audit committees with educational backgrounds in the IT sector were not relevant.